إشكالية تفعيل الاجتهاد في أحكام المواريث بوجود دلالة النّص القطعية: The Issue of Activating Ijtihad in the Rulings of Inheritance in the Presence of the Peremptory Significance of the Text - Raouane Azziz; Fajar Rachmadhani; Mualimin Mochammad Sahid (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
The verses of inheritance are texts that hardly have a parallel in the provisions of Sharia in terms of clarity and decisiveness in determining the share for each inheritor. Disputes arise over the understanding of these texts where some of the companions’ jurists went on to activate the mechanism of ijtihad even though the text is clear. Their jurisprudence gave us new rulings that are not mentioned either in the Qurʾān or in the Sunnah. Meanwhile, other jurists adhered to the apparent meaning of the texts. This study aims to reveal the reasons for establishing ijtihad, although there exist definitive texts on the provisions of inheritance, and to explain the path that each companion took in weighting their doctrine. To achieve these goals, this study relied on descriptive and analytical approaches. This study found that adherence to the apparent meaning of the texts in the rulings of inheritance is a principle that must be adhered to. Aside from that, using ijtihad in the provisions of inheritance with the presence of peremptory text is possible. It is activated according to the methodology that gives the Islamic ruling new dimensions upon its implementation and does not include either cancellation or change.